Amendment to Steps to Address Excessive Delays in the Completion of Article IV Consultations or Mandatory Financial Stability Assessments and Application to the Case of Argentina. (Policy Papers; Policy Paper ;, 2016)
Management has received a request from the Argentine authorities to publish documents on economic developments in the country prepared by Fund staff for informal Board briefings in 2013-15. The Argentine authorities see publication of these papers as part of their commitment to transparency and accountability in their operations. The documents were prepared pursuant to the Fund's policy on excessive delays in the completion of Article IV consultations and mandatory financial stability assessments, which requires that staff informally brief Executive Directors every 12 months on the economic developments and policies of relevant members. The objectives of the policy are to promote re-engagement with members with excessively delayed consultations, and to share information with the Board to help it fulfill its surveillance function. Under current policy, the briefing documents are not published. Instead, a short factual statement is issued in a press release, noting that the Board was given an informal staff briefing on the member's economy based on available information. Under the policy, the Fund decided against publication of the briefing documents since it was considered that publication could expose the Fund to a significant reputational risk if the analysis set out in the documents missed key vulnerabilities due to large information gaps created by the lack of consultation with the member. Also, outside audiences may not appreciate that the documents represent the views of staff, not the views of the Board, and do not constitute an Article IV consultation. A further concern was that publication could reduce the pressure on members to proceed with an Article IV consultation. In light of the current policy, any publication of these documents would require a change in policy approved by the Executive Board.